Psychosocial risk in construction workers in the city of Arequipa - García Vega, Kelly Yanina (2025)
In Peru, research on psychosocial risks has increased since the promulgation of the health and safety at work law, but a neglected sector is still the construction one. The aim of this study is to analyze psychosocial risk factors in construction workers in the city of Arequipa (Peru). A predictive associative investigation was designed, for which 72 workers from a private construction company were evaluated, to whom the Questionnaire for the Evaluation of Psychosocial Risks at Work (CoPsoQ Istas 21) was applied. It was found that the dimensions of psychosocial risk that obtained an unfavorable score were work pace, insecurity about working conditions, role clarity, quantitative demands, social support from superiors and double presence. It was concluded that the dimensions that have a significative impact on the incidence of accidents reported by workers are role clarity, leadership and predictability.